Sigil Software sebagai Pengembangan E-Modul Pembelajaran Matematika - Anisa Fitri; Netriwati Netriwati; Siska Andriani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2021)
Difficulties experienced by students to learn mathematics caused by the lack of practical and less interesting media used by lecturers in learning mathematics has an impact on the low student learning outcomes, especially in the matter of relations and functions. Therefore, “this study aims to determine the feasibility and response of students to the design of mathematics e-module learning devices using sigil software. This type of research is Research & Development (R&D) using the ADDIE model. Data collection techniques using interview techniques, questionnaires and tests. Validation was carried out by three material experts and two media experts. The validation results show that the e-module is suitable for use because it is good in terms of content, language, and presentation feasibility. The revised E-Module was tested on a small scale test (10 students) and continued with a large scale test (28 students). Student responses to e-modules also scored high on all indicators. It can be concluded, the e-module that has been developed is feasible and effective for use in the mathematics” learning process.